PENGARUH MEDIA QUIZIZZ DALAM PEMBELAJARAN FISIKA PADA MATERI MOMENTUM DAN IMPULS - Jeivi Riani Kasea; Treesje Katrina Londa; Jimmy Lolowang; Aswin Hermanus Mondolang; Sixtus Iwan Umboh; Patricia Mardiana Silangen (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aims to determine the Effect of Quizizz Media in physics learning on student learning outcomes in Momentum and Impulse material. The research method used in this study is quasi-experimental with Nonequivalent Control Group Design, namely research conducted in two classes, namely the experimental class and the control class. Research data were collected using test instruments in the form of essay test questions and data analysis techniques in the form of normality tests, homogeneity and hypothesis tests. The results of the study showed that; 1) From the results of the Quizizz learning media application process, there was a difference between the pretest and posttest scores where the posttest score was better, meaning that there was an increase after being treated; 2) A significant difference between the average posttest results of the experimental and control classes, the learning outcomes of students in the experimental class using Quizizz media obtained an average final test (posttest) of 83.87, while the control class using conventional methods obtained an average posttest of 65.96. Based on the average posttest results, learning using Quizizz media in its learning process has better results. Then a statistical analysis was carried out in the form of a t-test analysis (Independent sample t-test) obtained a sig. value (2-tailed) of 0.000 <0.05 so that H0 was rejected and H1 was accepted. Based on these results, it can be concluded that the Quizizz learning media has an effect on improving student learning outcomes.